Analysis of Manifestation of CC and CXC Chemokine Genes in Olive Flounders (Paralichthys olivaceus) Artificially Infected with VHSV during the Early Developmental Stage - Kim, Kyung-Hee (Dev Reprod, 2018)
Chemokines is a small protein that plays a major role in inflammatory reactions and viral infections as a chemotactic factor of cytokines involved in innate immunity. Most of the chemokines belong to the chemokine groups CC and CXC. To investigate the immune system of the olive flounder (Paralichthys olivaceus), an expression pattern specifically induced in the early developmental stages of analysis is examined using qRT-PCR. We also examined tissue-specific expression of both CC and CXC chemokine in healthy olive flounder samples. CC and CXC chemokine shows increased expression after immune-related organs are formed compared to expression during early development. CC chemokine was more highly expressed in the fin, but CXC chemokine showed higher expression in the gills, spleen, intestines, and stomach. Spatial and temporal expression analysis of CC and CXC chemokine were performed following viral hemorrhagic septicemia virus (VHSV) infection. CC chemokine showed high expression in the gills, which are respiratory organs, whereas CXC chemokine was more highly expressed in the kidneys, an immune-related organ. These results suggest that CC and CXC chemokine play an important role in the immune response of the olive flounder, and may be used as basic data for the immunological activity and gene analysis of it as well as other fish.